IMPLEMENTASI ETIKA PROFESI GURU MELALUI METODE TELADAN DALAM PEMBELAJARAN PAI DI SDN MURTAJIH 3 PAMEKASAN - Abd. Mukhid; Ocha Dwiyuan Sukma; Nasyathin; Zainul Hasan Atallibi (STKIP Subang, 2026)
Using a model method to study Islamic Religious Education (PAI) at SDN Murtajih 3 Pamekasan, this study aims to explain the ethics of the Islamic Religious Education (PAI) teacher profession and also consider the factors that influence and affect the ethics of the Islamic Religious Education (PAI) teacher profession. This qualitative study used data, interviews, and documents from PAI teachers and students. Data analysis included data dissemination, drawing conclusions, and data reduction, as well as ensuring triangulation techniques and sources. The results showed that teachers' views on discipline and responsibility were very important. Honesty and politeness were evident in their interactions with their students. In addition to teaching, teachers were kind to their students in their daily lives. Teachers arrived on time, spoke well, and explained the school's religious attitudes to students. The results showed that teachers behaved well beyond teaching. This model method improved student behavior, as indicated by increased student discipline, politeness, and respect for teachers, as well as increased student participation in class. Different students, teacher commitment, and the impact of the environment outside of school were helpful factors; however, different students and the application of consistent values were inhibiting factors. Therefore, to improve the quality of Islamic Religious Education (PAI) learning and develop the character of students in elementary schools, teachers must apply their professional ethics consistently in their learning activities.